Orientasi kewirausahaan dan kapabilitas pemasaran pada kinerja usaha kecil dan menengah: Peran faktor lingkungan yang dinamis sebagai pemoderasi - Asep Saifudin; Hasanuddin Pasiama (LPPM Swadaya Institute of Business and Communication, 2022)
The purpose of this study is to examine the impact of entrepreneurial orientation and marketing capabilities on the performance of small and medium-sized enterprises (SMEs), as well as how dynamic environmental factors moderate these relationships. The population was all managers or owners of SMES in Padang City. The sampling technique used a non-probability approach, namely purposive sampling. In the data analysis, 190 samples (response rate 84,44%) were used as a sample size. The Smart-PLS software is used in this study to perform variance-based structural equation modeling (VB-SEM). The findings show that (i) entrepreneurial orientation has a positive and significant effect on SME performance, (ii) marketing capabilities have a positive and significant effect on SME performance, and (iii) In these relationships, the role of dynamic environmental factors as a moderator is not supported. The managerial implications will be discussed later.